EFEKTIFITAS FUNGI MIKORIZA ARBUSKULA (FMA) SERTA PUPUK NITROGEN DAN FOSFAT TERHADAP PERTUMBUHAN SEMAI JABON (Anthocephallus cadamba Roxb.) Effectiveness of Arbuscula Mycorrhizal Fungi (AMF) Nitrogen and Phosphate Fertilizer toward Jabon ........ - Fransisca Yosina Regina Luturmas; Sri Wilarso Budi R.; Irdika Mansur (Jurnal Silvikultur Tropika, 2017)
Jabon (Anthocephallus cadamba Roxb.) is one of fast-growing species with high economical value, and well adapted on some of soil types. The aims of this research were to analyze the effectiveness of AMF species isolated from Samama (Anthocephallus macrophyllus (Roxb.) Havil) and to determine the favorable dose of nitrogen and phosphate fertilizer for Jabon growth. The research was conducted CRD-split plot design main plot was Acaulospora sp.1 (M1), Glomus sp.1 (M2), Acaulospora sp.2 (M3), Acaulospora sp.3 (M4), Glomus sp.2 (M5). While the fertilizer as the sub-plot, consist of control (P0), urea 0.5g+rockphosphat 2g (P1), urea 1g+rockphosphat 4g (P2). The result showed that AMF and fertilizer applications effectively improved Jabon grown, especially in height, stem diameter, and shoot dry weight. The interaction (M4P1) increased plant height 154.73%, diameter 75.38% and shoot dry weight 376.09% compared with control. P1 treatment was better for growth of Jabon that was inoculated by mycorrhiza. Acaulospora sp.1 (M1) originally from Samama without fertilizer had the best effectiveness for Jabon growth.Key words: Acaulospora, indigenous